DIRECTED RE-PROGRAMMING OF SOMATIC CELLS: ADVANTAGES AND LIMITATIONS OF INDUCED PLURIPOTENT STEM CELLS (REVIEW) - A. V. Korel; S. B. Kuznetsov (Сибирский научный медицинский журнал, 2019)
Stem cells are divided into embryonic and adult stem cells. The relevance of the use of stem cells in clinical practice has received new evidence in recent years however, the methods of obtaining stem cells for medical purposes cause ethical rejection. An alternative to the stem cells is the induced pluripotent cells. These cells are multipotential and comparable with features of embryonic stem cells but with additional advantages: their preparation allows to avoid many ethical problems associated with the use of embryonic material, their use reduces the risk of immune rejection. The possibility of somatic cells reprogramming into pluripotent stem cells opens the great prospects for regenerative medicine. An applying of directional reprogramming method makes possible to obtain practically any cell type from induced stem cells of the patient to use in autologous cell therapy. Induced pluripotent stem cells can also be used to model the human diseases and for screening of medicines. However, there are still a number of obstacles that need to be overcome before the use of induced pluripotent stem cells will be involved to routine clinical practice. This review examines the history of the creation of induced pluripotent stem cells and recent advances in the reprogramming of somatic cells, as well as the challenges that need to be overcome in order to apply this strategy in clinical practice.